2019
DOI: 10.17511/joog.2019.i03.01
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between placental location and maternal fetal outcome

Abstract: Background: Placenta is the vital link between fetus and the uterine wall. Based on location, it can be classified as anterior, posterior, lateral, fundal and low lying. Placental location can be easily determined in the antenatal period using ultrasound. Materials and Methods: Design: Prospective observational study. Study period: One year from January 2018 to February 2019 in a tertiary hospital in Salem district of Tamilnadu. Study population: After informed consent, 200 women with singleton pregnancy of ≥2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Still at variance, Adekanmi et al (2022) in their longitudinal study design, noticed that placental location was significantly associated with fetal weight (p = 0.002) and posterior placenta was noted to produce one of the highest fetal weights (3.00 ± 0.65 kg). In another longitudinal study, Dhingra et al (2019) observed that posterior placental location was significantly associated with low fetal weight (p < 0.001) including Soleimani et al (2021) who also recorded a significant correlation between placental location and fetal weight (p < 0.001) and that fundal placental location was seen more in fetuses with lower weights than anterior and posterior placentas. Concurring with findings of the present study, Behzadmehr et al (2020) affirmed that there was no relationship between placental location and fetal weight (p = 0.555) even though fetal weight was higher in anterior placental location.…”
Section: Discussionmentioning
confidence: 91%
“…Still at variance, Adekanmi et al (2022) in their longitudinal study design, noticed that placental location was significantly associated with fetal weight (p = 0.002) and posterior placenta was noted to produce one of the highest fetal weights (3.00 ± 0.65 kg). In another longitudinal study, Dhingra et al (2019) observed that posterior placental location was significantly associated with low fetal weight (p < 0.001) including Soleimani et al (2021) who also recorded a significant correlation between placental location and fetal weight (p < 0.001) and that fundal placental location was seen more in fetuses with lower weights than anterior and posterior placentas. Concurring with findings of the present study, Behzadmehr et al (2020) affirmed that there was no relationship between placental location and fetal weight (p = 0.555) even though fetal weight was higher in anterior placental location.…”
Section: Discussionmentioning
confidence: 91%
“…Dhingra et al studied 200 pregnant women, 42% of placenta were situated in fundus, 30% were anterior, 18% were lateral, 8% were posterior and 2% were low lying. 10 Gestational hypertension was present in 22%, 13%, 12% in lateral, anterior and posterior placental location respectively. Preeclampsia was seen in 22% in lateral placental location.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the uterine blood supply plays a significant role in the success of placental blood flow and pregnancy [ 2 ]. Hence, abnormalities in the placental implantation may affect the blood supply of the placenta, leading to adverse maternal and fetal outcomes, such as gestational hypertension, preeclampsia, gestational diabetes, malpresentation, malposition, preterm birth, small for gestational age, fetal growth retardation, low birth weight, intrauterine fetal death, and stillbirth [ 3 ].…”
Section: Introductionmentioning
confidence: 99%